Bioaccumulation investigation of bisphenol A in HepG2 cells and zebrafishes enabled by cobalt magnetic polystyrene microsphere derived carbon based magnetic solid-phase extraction. Issue 4 (20th December 2019) - Niu, Panhong; Lu, Xiaofeng; Liu, Bingtao; Li, Yijing; Liang, Xiaojing; Wang, Shuai; Guo, Yong
Abstract : Cobalt magnetic polystyrene microsphere derived carbon (C–Co@PST) with a core–shell structure was employed to investigate the bioaccumulation of bisphenol A (BPA) in HepG2 cells and zebrafishes based on a magnetic solid-phase extraction (MSPE) method. Abstract : A magnetic solid-phase extraction (MSPE) technique coupled with high performance liquid chromatography (HPLC) was developed and used for bioaccumulation investigation of bisphenol A (BPA) in HepG2 cells and zebrafishes. Cobalt magnetic polystyrene microsphere derived carbon (C–Co@PST) as an adsorbent was prepared by in situ polymerization reaction and further annealing treatment. Scanning electron microscopy, energy-dispersive X-ray spectroscopy, Fourier transform infrared spectrometry, X-ray photoelectron spectroscopy and X-ray diffraction were employed to confirm successful synthesis of C–Co@PST. A series of extraction parameters including the amount of the sorbent, the type of elute, extraction time and elution time were investigated to achieve high extraction efficiency. C–Co@PST based MSPE combined with HPLC was successfully established for bioaccumulation research of BPA in living creatures. It was found that the bioconcentration values of BPA in HepG2 cells underwent an increase, then a decrease, and finally reached an equilibrium level of 11.60 μg kg −1 at 8 h. The concentration of BPA in zebrafishes increased ranging from 6.05 μg kg −1 to 31.84 μg kg −1 over a culture time from 1 h to 12 h. Furthermore, linear and exponential models were employed to analyse the bioconcentration variation of BPA in organisms over the exposure time. Mathematical models have been developed to predict the transfer characteristics of BPA.